The Rise of Kandong Girls: A Qualitative Examination on the Lives of Prostitutes - MOYAO, WARREN (IJRDO - Journal of Social Science and Humanities Research, 2021)
This paper deals with the problem of prostitution in Barangay Abatan, Buguias, Benguet. The main objective of this study is to gain insights into how the Kandong Girls live their lives through the understanding of the factors that pushed them to engage in prostitution. Also, it aims to understand the impact of the sex profession on their personal lives. This study made use of the qualitative research method through the case study design. The participants of this research were three sex workers in Abatan, Buguias, Benguet that were selected through purposive sampling. The major instrument for data collection was the interview guide. Using axial coding, the data were related together in order to reveal codes, categories, and subcategories ground within the participants’ voices. The findings revealed that the factors that pushed the participants to become Kandong Girls are their willingness to sustain their family’s needs, the idea of having a good income and easy money, being fascinated by their friends, survival, and escaping from physical violence experienced inside their home. Moreover, being engaged in the sex profession has led them to have a deceitful lifestyle, having a stained image, and being vulnerable to sex-related diseases.